2022
DOI: 10.3892/etm.2022.11396
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin suppresses TNF‑α‑induced inflammatory injury and senescence of nucleus pulposus cells via the Sirt6/NF‑κB pathway

Abstract: Luteolin (3',4',5,7-tetrahydroxy flavone) is a flavonoid, which is widely distributed in various plants including flowers, vegetables, and medicinal herbs and spices. Luteolin can be applied in the treatment of various diseases due to its multiple biological activities, such as anti-inflammatory, anticancer, and antioxidative activity. However, its role in intervertebral disc degeneration has not been previously reported. Therefore, the purpose of the present study was to explore the effects of luteolin on Tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…A previous investigation indicated that luteolin might act on TNF and medicate the HIF-1 pathway implicated in the treatment of HUA [14]. Recent research has indicated that luteolin can effectively reduce the expression of proinflammatory factors IL1B and IL-6 to mitigate TNF-α-induced cellular inflammatory injury [72]. Rutaecarpine, an alkaloid extracted from the unripe fruit of E. rutaecarpa, possesses an antiinflammatory function [73].…”
Section: Discussionmentioning
confidence: 99%
“…A previous investigation indicated that luteolin might act on TNF and medicate the HIF-1 pathway implicated in the treatment of HUA [14]. Recent research has indicated that luteolin can effectively reduce the expression of proinflammatory factors IL1B and IL-6 to mitigate TNF-α-induced cellular inflammatory injury [72]. Rutaecarpine, an alkaloid extracted from the unripe fruit of E. rutaecarpa, possesses an antiinflammatory function [73].…”
Section: Discussionmentioning
confidence: 99%
“…Luteolin, a natural plant extract, has demonstrated various biological and anticancer effects. 27 In this study, we treated PCa cells with luteolin in vitro and constructed lentiviral sh-TFEB cell lines to explore the effects of luteolin and TFEB on PCa. Our findings revealed that luteolin-induced ferroptosis in PCa cells by promoting TFEB nuclear translocation and enhancing ferritinophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Research and development of new antitumor mechanisms and stable drugs are urgently needed. Luteolin, a natural plant extract, has demonstrated various biological and anticancer effects 27 . In this study, we treated PCa cells with luteolin in vitro and constructed lentiviral sh‐TFEB cell lines to explore the effects of luteolin and TFEB on PCa.…”
Section: Discussionmentioning
confidence: 99%
“…In TNF‐α induced NPC inflammatory stress experiment, the nuclear translocation of NF‐κB p‐p65 protein increased, the apoptosis markers Bax, Caspase 3, apoptosis protease activating factor 1 (Apaf1), and aging related proteins p16, p21, and p53 were upregulated, and the expression of antiapoptosis protein Bcl‐2 was downregulated. These changes accelerated cell senescence and apoptosis, and the nuclear translocation of p65 may be mediated by TRIM14 (Chen, Li, et al, 2022; Xie et al, 2022; Zhang, Tong, et al, 2021; Zhu et al, 2019).…”
Section: Cell Autophagy and Iddmentioning
confidence: 99%